2020
DOI: 10.1021/acs.analchem.9b04946
|View full text |Cite
|
Sign up to set email alerts
|

Combination of an Artificial Intelligence Approach and Laser Tweezers Raman Spectroscopy for Microbial Identification

Abstract: Raman spectroscopy is a nondestructive, label-free, highly specific approach that provides the chemical information on materials. Thus, it is suitable to be used as an effective analytical tool to characterize biological samples. Here we introduce a novel method that uses artificial intelligence to analyze biological Raman spectra and identify the microbes at a single-cell level. The combination of a framework of convolutional neural network (ConvNet) and Raman spectroscopy allows the extraction of the Raman s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
84
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 56 publications
0
84
0
Order By: Relevance
“…We have applied a combination of single-cell Raman microspectroscopy and RF machine learning strategy for classification of six prokaryotic species chosen from a variety of phyla and for identification in a mixed population envisaging environmental samples. Recently, CNN, a deep learning technique, was used to classify Raman spectra of 30 clinically relevant bacteria including methicillin-resistant Staphylococcus aureus ( Ho et al., 2019 ) and of 14 microorganisms (two bacteria, five archaea, and seven fungi) ( Lu et al., 2020 ). The significance of our work compared to these studies is threefold.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We have applied a combination of single-cell Raman microspectroscopy and RF machine learning strategy for classification of six prokaryotic species chosen from a variety of phyla and for identification in a mixed population envisaging environmental samples. Recently, CNN, a deep learning technique, was used to classify Raman spectra of 30 clinically relevant bacteria including methicillin-resistant Staphylococcus aureus ( Ho et al., 2019 ) and of 14 microorganisms (two bacteria, five archaea, and seven fungi) ( Lu et al., 2020 ). The significance of our work compared to these studies is threefold.…”
Section: Discussionmentioning
confidence: 99%
“…First, we aimed at developing an accurate classification model applicable to a complex environmental system composed of multiple prokaryotic species. As shown in Table 1 , the prokaryotic species used in this work cover microbial-ecologically relevant species that belong to Proteobacteria , Firmicutes , Deinococcus-Thermus , Crenarchaeota , Euryarchaeota , and Thaumarchaeota , although focus in the previous studies was placed primarily on pathogenic or human-related microorganisms only from Proteobacteria and Firmicutes ( Ho et al., 2019 ; Lu et al., 2020 ). The classification accuracy exceeding 98% achieved by our approach for the mixed prokaryotic population gives hope for in situ identification of specific prokaryotic groups (e.g., archaea) at the single-cell level without the need for time-consuming, destructive analysis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thrift et al demonstrated single-entity analysis by using convolutional neural network-assisted surface-enhanced Raman spectroscopy techniques for detecting ultralow (< nanomolar) concentrations of Rhodamine 800 [239]. Similarly, Lu et al reported identifying microorganisms at single cellular level using laser tweezer spectroscopy with convolutional neural networks, with a classification accuracy of ~95% [240]. Pandit et al demonstrated highly accurate detection of proteins present in low concentrations, without the use of any bioreceptor by using carbon-dot sensors assisted by a variety of machine learning algorithms [241].…”
Section: Machine Learning For Nano-biosensorsmentioning
confidence: 99%